RELIGIOUS SENTIMENT AND SOCIAL CONTROL IN INDONESIA - Gultom, Eva Solina; Hadi, Arie Toursino (Seshiski: Southeast Journal of Language and Literary Studies, 2021)
Blasphemy cases toward minority have been significantly rising in Indonesia. Religion has already become one of the aspects that urge sustainable conflicts among other pluralistic societies. Each side, the actors and the victims, have struggled to defend their truth without putting their conscience aside humanity or tolerance. This cost is too much comparing to what our nation did to fight for democracy. One of recent blasphemy issues that successfully went viral is a video showing a popular Islamic cleric, Abdul Somad telling a crowd that the Christian crucifix is the dwelling place for a genie. Surely, this video has sparked an angry reaction from Christians. However, this action met some contrary responses from our society. This study aims to analyze how religious sentiments could show its power or authority to affect social control that happened in Indonesia. This study applied Bourdieu’s theory of social capital and power reflecting the strategies of resistance which may happen between pros and cons by combining some perspectives.